Informatics in Control, Automation and Robotics 13th International Conference, ICINCO 2016 Lisbon, Portugal, 29-31 July, 2016 (Lecture Notes in Electrical Engineering,, 2018)
The book addresses the latest advances in research and development in the field of informatics in control, robotics and automation. With more than twenty revised and extended articles covering the theoretical aspects as well as applications and their implementation, it offers a factual and well-balanced overview of the state of the art in the field. In addition, it highlights the trends in control of intelligent robots. The book is an up-to-date source of information and inspiration for researchers, engineers and PhD students.